Factors Causing Delays in BPJS Health Inpatient Claims at Dr. Harjono S Regional General Hospital in Ponorogo Regency - Ike Wahyu Septian; Dwi Nurjayanti (program studi Rekam Medis dan Infomasi Kesehatan ITSK RS dr Soepraoen Malang, 2025)
Pending inpatient BPJS Health claims pose a financial and operational challenge for hospitals. At RSUD Dr. Harjono S Ponorogo, 228 pending claims were identified in November 2024 out of 1,335 total claims. This issue was caused by incomplete supporting documents, coding errors, and non-specific medical diagnoses and procedures. This study used a descriptive qualitative approach through observation and interviews. The sample consisted of four claims officers and 228 inpatient pending claim files. The sampling technique used was purposive sampling. Data were analyzed through data reduction, presentation, and conclusion drawing. The study revealed several contributing factors: (1) Man lack of accuracy and training among staff; (2) Method suboptimal claim procedures; (3) Material incomplete supporting documents; (4) Machine information system disruptions; and (5) Money delayed claim payments. The primary causes of pending inpatient claims are incomplete medical documentation and inaccurate coding. Improvements are needed in staff training, claim procedures, and system integration between hospitals and BPJS Health.